Development of Wetland Contextual Interactive Learning Media with Student Activity Monitoring - Harja Santana Purba; Sari, Delsika Pramata; Novan Alkaf Bahraini Saputra; Syahril Hanla Azis; R. Ati Sukmawati (JTP - Jurnal Teknologi Pendidikan, 2023)
The purpose of this study was to develop a web-based interactive learning multimedia for statistics material for 8th grade. The material was presented with a contextual approach so that students could connect material concepts with real-life problems to instill an understanding of the material. Nothing that excels in this learning media was monitoring student activities while studying, such as student progress in learning the material, activities that have been and have not been carried out in the learning series, and monitoring of keyboard and mouse activities. Learning media was developed using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Evaluation). The learning media functionality was tested using the Black Box method. Based on the results of testing all features, it could be concluded that the developed learning media application can function well with very high validity. Where the results of media validation were 90.3% and material validation was 87.5%. Furthermore, the developed interactive learning media is suggested to be able to display monitoring of activities that have been done by students in their respective accounts.